Formation of secondary nonsulfide zinc ore in Cho Dien Pb-Zn deposits - Lien, Nguyen Thi; Pho, Nguyen Van (Vietnam Journal of Earth Sciences, 2018)
In Viet Nam, non-sulfide zinc ore in the Cho Dien deposit has been exploited for a long time. Up to the present, zinc ore remains the major exploited ore in Cho Dien. There are numerous studies of Pb-Zn ore in Cho Dien. However, most of the studies have dedicated only to description of mineralogical and chemical composition of Pb-Zn ore. There has been no publication on this non-sulfide zinc ore. Based on the mineralogical studies, the content of Pb and Zn in groundwater determined by reflective microscope, SEM, EPMA and ICP-MS methods, the study explained the formation of secondary non-sulfide zinc ore in the Cho Dien deposit. Strong weathering process makes the upper part of ore bodies completely oxidized. Difference in geochemical behavior of lead (Pb) and zinc (Zn) in the oxidation process of Pb-Zn ore is the reason to form non-sulfide zinc ore in the Cho Dien deposit. Oxidation of primary Pb-Zn ore is mainly sphalerite, pyrite, galena minerals which creates a low pH environment and transforms of zinc from immobile (sphalerite - ZnS) to mobile (Zn2+) and retained in solution under acid pH conditions whereas lead has the tendency to form soluble minerals (anglesite, cerussite). The acid neutralization actions of the surrounding rocks make zinc precipitate, to form secondary non-sulfide zinc minerals.ReferencesAndreas Nuspl, 2009. Genesis of nonsulfide zinc deposits and their future utilization (www.geo.tu-frei berg.de/oberseminar/OS_09/Andreas_Nuspl.pdf.Boland M.B., et al., 2003. The Shaimerden supergene zinc deposit, Kazakhstan: Economic Geology, 98(4), 787-795.Chau N.D., Jadwiga P., Adam P., D.V. Hao, L.K. Phon, J. Paweł, 2017. General characteristics of rare earth and radioactive elements in Dong Pao deposit, Lai Chau, Vietnam, Vietnam J. Earth Sci., 39(1), 14-26.Dao Thai Bac, 2012. Characteristics and distribution law of lead-zinc metallogenic fomations in Viet Bac region. Doctoral thesis.Heyl A.V., Bozion C.N., 1962. Oxidized zinc deposits of the United States, Part 1. General Geology: U.S. Geological Survey Bulletin 1135-A.Hoa T.T., et al., 2010. By-products in lead-zinc and copper ores of Northeast Vietnam. J. Sci. of the Earth,  289-298 (in Vietnamese).Hoang Minh Thao, Tran Thi Hien, Dao Duy Anh, Pham Thi Nga, 2017. Mineralogical characteristics of graphite ore from Bao Ha deposit, Lao Cai Province and proposing a wise use. Vietnam J. Earth Sci., 39(4), 324-336.Jurjovec J., et al., 2002. Acid neutralization mechanisms and metal release in mine tailings: A laboratory column experiment: Geochimica et Cosmochimica Acta, 66, 1511-1523.Large D., 2001. The geology of non-sulphide zinc Deposits - an Overview: Erzmetall, 54(5), 264-276.Maria Boni, 2003. Nonsulfide Zinc Deposits: a new - (old) type of economic  mineralization. Society for geology applied to mineral deposits (SGA) News, Number 15. https://www.e-sga.org/fileadmin/sga/newsletter/news15/art01.html.McPhail D.C., et al., 2003, The geochemistry and mobility of zinc in the regolith: in Roach, I.C., ed., Advances in Regolith, 287-291.Murray W. Hitzman, et al., 2003. Classification, genesis, and exploration guides for non-sulfide zinc deposits: Economic Geology, 98(4), 685-714.Nguyen V.P., 2013. Wet tropical wethering in Viet Nam. Natural Science and Technology Publisher.Nicola Mondillo, 2013. Supergene Nonsulfide Zinc-Lead Deposits: The Examples of Jabali (Yemen) and Yanque (Peru). Doctoral thesis.Nordstrom D.K., Alpers C.N., 1999. Geochemistry of acid mine waste. Review in Economic Geology, the environmental geochemistry of ore deposits/Eds. G.S.Plumlee, M.J. Logsdon. Part A: Processes, techniques, and health issues, 6A, 133-160.Reynolds N.A., et al., 2003. The Padaeng Supergene Nonsulfide Zinc Deposit, Mae Sod, Thailand. Economic Geology, 98(4), 773-785.Sangameshwar S.R., Barnes H.L., 1983. Supergene Processes in Zinc-Lead-Silver Sulfide Ores in Carbonates: Economic Geology, 78, 1379-1397.Stumm W., Morgan J.J., 1996. Aquatic Chemistry, Third Edition. John Wiley & Sons, New York, NY.Takahashi T., 1960. Supergene alteration of zinc and lead deposits in limestone: Economic Geology, 55, 1083-1115.Thornber M.R. and Taylor G.F., 1992. The mechanisms of sulphide oxidation and gossan formation, in: Butt, C.R.M., and Zeegers H., (Eds.)., Regolith exploration geochemistry in tropical and subtropical terrains, in Govett G.J.S., ed., Handbook of exploration geochemistry: Amsterdam, Elsevier, 4, 119-138.Tran Trong Hoa, 2005. Potential assessment of By- products in lead-zinc and copper deposits of   Northeast Vietnam. Final report.Tran Tuan Anh, 2010. Studying accompanying component in the types of potential deposits of basic metals and precious - rare metals of north Viet Nam to improve the efficiency of mining and environmental protection. Final report. KC.08.24/06-10.Tran Tuan Anh, et al., 2011. Mineralogical and geochemical characteristics and forming conditions of lead - zinc deposits  in Lo Gam structure, northern Vietnam. J. Sci. of the Earth, 33(3DB), 393-408 ( in Vietnamese).Vito Coppola et al., 2009. Nonsulfide zinc deposits in the Silesia - Cracow district, Southern Poland. Springer Link, 44, 559-580.Vito Coppola, et al., 2007. Non-sulfide zinc deposits in Upper Silesia, Southern Poland. Proceeding of the Ninth Biennial SGA Meeting, Dublin, 1401-1404.Williams P.A., 1990. Oxide zone geochemistry: Ellis Horwood Ltd., Chichester, UK, 286p.